Lanxess among the bidders for AkzoNobel's speciality chemicals unit. Issue 2 (February 2018) - Unknown
Abstract : According to reports in the German and international business press, Cologne-based chemicals producer Lanxess AG has joined forces with US private equity firm Apollo Global Management to submit an offer for all or part of the Specialty Chemicals division of Dutch company AkzoNobel NV. No information was available on the size of the bid, but AkzoNobel is said to value the unit at between €8 billion and €12 billion [ ADPO, January 2018].